Infiltrating CD16+ Are Associated with a Reduction in Peripheral CD14+CD16++ Monocytes and Severe Forms of Lupus Nephritis (2016)
ABSTRACT: Our aim was to characterize glomerular monocytes (Mo) infiltration and to correlate them with peripheral circulating Mo subsets and severity of lupus nephritis (LN). Methods. We evaluated 48 LN biopsy samples from a referral hospital. Recognition of Mo cells was done using microscopic view and immunohistochemistry stain with CD14 and CD16. Based on the number of cells, we classified LN samples as low degree of diffuse infiltration (<5 cells) and high degree of diffuse infiltration (≥5 cells). Immunophenotyping of peripheral Mo subsets was done using flow cytometry. Results. Mean age was years and the mean SLEDAI was . The most common SLE manifestations were proteinuria (91%) and hypocomplementemia (75%). Severe LN was found in 70% of patients (Class III, 27%; Class IV, 43%). Severe LN patients and patients with higher grade of CD16+ infiltration had lower levels of nonclassical (CD14+CD16++) Mo in peripheral blood. Conclusions. Our results might suggest that those patients with more severe forms of LN had a higher grade of CD14+CD16+ infiltration and lower peripheral levels of nonclassical (CD14+CD16++) Mo and might reflect a recruitment process in renal tissues. However, given the small sample, our results must be interpreted carefully.